Do shame and perfectionistic self-presentation explain the link between early affiliative memories and eating psychopathology? - Ferreira, C. (2017)
This study explored a model examining the impact that early affiliative memories (with family and peers) presents on eating psychopathology, and whether this link is carried by the mechanisms of external shame and body image-related perfectionistic self-presentation. This study’s sample comprised 480 female college students, who completed the self-report measures of interest. Path analyses’ results revealed that this model accounted for 48% of disordered eating’s variance. Furthermore, results showed that 26% of external shame was explained by early memories of warmth and safeness, and that 19% of body image-related perfectionistic self-presentation was explained by the lack of recall of these affiliative memories, through increased levels of external shame. These findings seem to suggest that the lack of these positive memories is associated with higher levels of shame (feelings of inferiority and unattractiveness), and with higher tendencies to adopt body image-related perfectionistic strategies, that seem to explain excessive eating concern and rigid control of one’s eating behaviours. This study offers important insights for future research and for the development of intervention programs, by revealing the importance of assessing and targeting shame and perfectionistic strategies and suggesting the importance of promoting adaptive emotion regulation strategies to deal with adverse memories.